Occult Esophageal Squamous Cell Carcinoma Presenting with Multiple Bony Osteolytic Lesions Clinically Mimicking Multiple Myeloma: A Diagnostic Dilemma - Lyngdoh, Bifica Sofia; Dey, Biswajit; Raphael, Vandana; Tiewsoh, Iadarilang (Journal of Laboratory Physicians, 2020)
Bone metastasis as an initial presentation of esophageal carcinoma is uncommon. In the absence of typical presentations like dysphagia, these cases may lead to diagnostic dilemmas both for the clinicians and pathologists. Here, we report a case of disseminated metastasis of esophageal squamous cell carcinoma to the bone in a 47-year-old female, who presented with multiple osteolytic lesions and clinically mimicking multiple myeloma. A detailed diagnostic work-up established the diagnosis of esophageal squamous cell carcinoma.
Keywords: esophageal squamous cell carcinoma; dysphagia; multiple myeloma